Comparison of coping strategies and emotion regulation tendencies among opium users, methadone maintenance treatment clients and normal individuals - Sadi Azizi; Alireza Maghsoudloo; Shahab Baheshmat (Gonabad University of Medical Sciences, 2019)
Substance abuse is also related to psychological skills that affect the treatment process. Identifying the role of these skills can be useful for the development of a better intervention. This purpose of this study was to compare the coping strategies and emotion regulation profiles among opium users, methadone maintenance treatment clients, and normal individuals. The sample was selected among patients and their accompanies-relatives or friends-as attending to Sari substance abuse treatment centers in spring 2016 to start or continue professional treatment. By using convenience sampling method, participants were assigned to three groups: opium users (n= 43), methadone maintenance treatment clients (n= 45), and control group (n= 43). Measuring tools included coping inventory for stressful situations and the difficulties in emotion regulation scale for all participants in the three groups. Significant differences were observed between the control and experimental groups: compared to the control group, opium users and methadone maintenance treatment clients had more emotion regulation difficulties and more adopted avoidance and emotion-focused coping strategies. By exploring the variables associated with the onset, persistence, and severity of substance abuse, the findings suggested groundwork for further researches which could be incorporated in prevention, treatment, and rehabilitation evidence-based methods to ameliorate the rate of substance abuse and dependency and related harms.